Relationship between heart rate, heart rate variability, heart rate recovery and global positioning system determined match characteristics of male, elite, African badminton players - Bisschoff, C. A.; Coetzee, B.; Esco, M. R. (International Journal of Performance Analysis in Sport, 2016)
The primary aim of this study was to investigate the relationship between heart rate (HR), heart rate variability (HRV), heart rate recovery (HRR) and global positioning system (GPS) determined match characteristics of male, elite, African, singles badminton players. Twenty-two players were fitted with a Fix Polar Heart Rate Transmitter Belt and a GPS unit to record HR and court movements every second during each match. Results revealed a strong, non-significant canonical correlation of Rc = 0.99 (p = 0.257) between HR, HRV, HRR and GPS determined match characteristics. The total redundancy values showed that 38.47% of the variance in the nine GPS-related variables could be accounted for by the ten HR-related variables. Likewise 38.88% of the variance in the HRrelated variables could be accounted for by the nine GPS-related variables. Furthermore, distance covered at a low exercise intensity, the amount of low intensity accelerations and player load were highlighted as the highest external match load-related contributors whereas Ln-HFnu power, peak HF (Hz) and Ln-LFnu/Ln-HFnu were identified as the highest internal match load-related contributors. In conclusion, when evaluating badminton internal match loads practitioners should consider and correct for GPS determined external match loads of players to prevent clouded and inaccurate conclusions of autonomic nervous system behaviour from occurring.